DIFERENSIASI PEMBELAJARAN DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR: KAJIAN LITERATUR SISTEMATIS - Chindytia; I Made Riki Nanjaya Diputra; Ni Ketut Rai Laraningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Differentiated instruction is a key pillar of the Kurikulum Merdeka (Freedom Curriculum) designed to accommodate the diverse needs, interests, and learning profiles of elementary school students. Despite policy implementation since 2022, field-level challenges remain uncomprehensively synthesized. This study aims to: (1) identify the concepts and principles of differentiated instruction within the Kurikulum Merdeka framework; (2) map evidence-based implementation strategies; and (3) describe challenges and solutions supported by empirical evidence. A Systematic Literature Review (SLR) using the PRISMA protocol was employed. Searches across Google Scholar, GARUDA, and DOAJ databases yielded 248 articles; after four-stage screening, 25 articles indexed in Sinta 1–4 (2022–2026) were included. Results reveal three differentiation dimensions content, process, and product that must be implemented in an integrated manner grounded in diagnostic assessment. Eight strategies proved effective, led by flexible grouping (cited in 18/25 articles) and beginning-of-unit diagnostic assessment (19/25 articles). The greatest challenge is limited teacher pedagogical competence, addressable through lesson study–based professional learning communities and the Merdeka Mengajar platform. This review produces evidence-based synthesis directly applicable to teachers, school principals, and policymakers seeking to optimize differentiated instruction at the elementary school level.